Les Cérémonies du mariage chez les Kel-Ajjer du Sud-Est de l'Algérie Étude ethnolinguistique d'une alchimie entre tradition et modernité - Vaudour, Catherine (AfriqueS, 2018)
The rites of marriage are a privileged social time that the ethnolinguist's study takes as a subject of investigation among Tuaregs from Ajjer in South east of Algeria. Marriage ceremonies involve a great number of rituals which allows close study of social groupings, in particular the status/position of women. In the Tuareg's culture, a traditional wedding is very expensive for the bridegroom and his family. This situation has produced a new custom: the institution of collective weddings initiated and supported financially by the state, associations and also by gifts from shopkeepers. However, we observe some traditions remain even with these collective weddings. In this area, muslim religion disrupts the position of women, showing a real change in traditional values. The presentation of social changes allows the showing on the one hand of how a culture adapts to new circumstances, and on the other how some traditions are preserved. The particular status of woman who after marriage find themselves alone-widowed or repudiated, or more rarely separated-shows that in Tuareg culture the liberty of woman, usually vouched for in the past, is actually constrained by law and religion in Algerian society.